TINJAUAN YURIDIS TERHADAP BENTUK PERTANGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA PENYALAHGUNAAN KARTU KREDIT MILIK ORANG LAIN - Ilham, Khairul; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The use of money in people's lives is the most important basic requirement in meeting their needs.But in its journey, the use of cash has a high risk, for example theft, robbery and forgery. Credit cards are akind of card as a physical substitute for money. Various modes of credit card crime can occur often in themidst of society and the development of sophisticated technology, the modes of credit card crime oftenincrease in type. Carding is a form of crime that uses someone else's credit card to spend without theknowledge of the owner. The development of Carding cases in Indonesia is moving very fast. According tothe results of the latest research conducted by the company Security Clearcommerce(www.clearcommerce.com) based in Texas, stated that Indonesia was in the first place of origin of theperpetrators of Cyber Fraud. He also added that around 20 percent of total credit card transactions fromIndonesia via the internet are Cyber Fraud. Therefore, sufficient knowledge is needed to explore theproblems of this credit card crime for the community as well as law enforcement carried out by lawenforcement officials.Keywords: Credit Cards, Internet, Carding, Cyber Fraud